Recruitment Process for Educators at Special Schools (SLB) Gorontalo City - Maya Lamusu; Lisda Van Gobel; Yahya Antu (International Journal of Sustainable Applied Sciences, 2023)
The purpose of this study is to study and find out how the recruitment process of teaching staff at the Gorontalo City Special School (SLB). The sub-focus in this study is the process of planning, implementation and placement. The research method used in this study is qualitative descriptive. While data collection uses observation, interview and secondary data recording techniques. In accordance with the type of research used, the data analysis technique used is a qualitative analysis technique. The results showed that from the aspect of planning, implementation and placement were not effective or did not support the Recruitment Process. The things suggested in this study are expected by local governments, especially the Education Office, to pay attention to obstacles that can hinder the recruitment process of teaching staff, especially in SKB, if this condition is allowed to continue and no solution is found, it will affect the quality of education in SKB Gorontalo City.